1996
DOI: 10.1080/00914039608031303
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Zn2+Ions with Phospholipid Multilayers

Abstract: Phospholipids are large natural amphipathic molecules which, in contact with water, assemble into higher molecular aggregates. The most relevant one is the bilayer for its relation to the structure, properties and functions of cell membranes. Given their structural complexity phospholipid bilayers are usually used as models for studying how biologically relevant chemicals affect the structure and functions of biomembranes. Zn is a trace element essential for the functional integrity of cell membranes. It is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…It therefore can be concluded that the toxicity of Cd 2þ is not specific at the membrane level and it is exerted by several mechanisms. A comparison of the effects of Cd 2þ with the effects of Cu 2þ , Zn 2þ , Hg 2þ and Pb 2þ ions on phospholipid bilayers, DMPC LUV and IUM clearly shows that Cd 2þ , followed by Pb 2þ , induced the highest structural perturbation in all these systems [11,12,14,15]. These results agree with the recognition of cadmium as one of the most toxic environmental pollutants [8,23].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It therefore can be concluded that the toxicity of Cd 2þ is not specific at the membrane level and it is exerted by several mechanisms. A comparison of the effects of Cd 2þ with the effects of Cu 2þ , Zn 2þ , Hg 2þ and Pb 2þ ions on phospholipid bilayers, DMPC LUV and IUM clearly shows that Cd 2þ , followed by Pb 2þ , induced the highest structural perturbation in all these systems [11,12,14,15]. These results agree with the recognition of cadmium as one of the most toxic environmental pollutants [8,23].…”
Section: Discussionsupporting
confidence: 87%
“…Intact human erythrocytes incubated with the metal ions were observed by scanning electron microscopy (SEM) while their IUM and DMPC LUV were studied by fluorescence spectroscopy. These systems and techniques have been used in our laboratories to determine the interaction with and the membrane-perturbing effects of other metal ions such as Zn 2þ [11], Cu 2þ [12], Hg 2þ [13], Al 3þ [14], and Pb 2þ [15].…”
Section: Introductionmentioning
confidence: 99%
“…Intact human erythrocytes incubated with this compound were observed by scanning electron microscopy (SEM) while their IUM and DMPC LUV were studied by fluorescence spectroscopy. These systems and techniques have been used in our laboratories to determine the interaction with and the membraneperturbing effects of other metal ions such as Zn 2+ [11], Cu 2+ [12], Hg 2+ [13], Al 3+ [14], Pb 2+ [15] and Cd 2+ [16].…”
Section: Introductionmentioning
confidence: 99%